Interactive videos and student learning activity in Buddhist religion classes at SMP N 21 Pesawaran - Bayu Kesumo; Susanto Susanto; Widiyanto Widiyanto (Universitas Sebelas Maret, 2025)
Teachers play a crucial role in the learning process, not only as conveyors of material, but also as facilitators and motivators to encourage student learning activity. Learning activity is an important indicator of learning success because active students tend to understand the material more easily, engage in critical thinking, and show interest and responsibility for learning. One way to increase learning activity is to use innovative learning media, such as interactive videos. This study aims to determine the effect of using interactive videos on student learning activity and to measure the extent of its influence in Buddhist Education at SMP Negeri 21 Pesawaran. This study used a quantitative approach with a survey method. The research subjects were all Buddhist students, totalling 30 respondents. The data collection instrument used was a questionnaire with a Likert scale, and the data were analysed using simple linear regression techniques. The results showed that there was a positive and significant effect between the use of interactive videos and student learning activity, with a contribution value of 18.6%. This means that the higher the optimisation of interactive video use in the learning process, the higher the students' learning activity. These findings confirm that interactive videos can be an effective and enjoyable learning medium, capable of increasing students' attention, interaction, and engagement during learning. Therefore, it is recommended that teachers consistently and creatively integrate interactive videos into the learning process to achieve maximum learning outcomes.